Analisis Kestabilan Pemodelan Matematika Penyebaran Word Of Mouth Berbasis Brand Community - Daniel Alexander; Eti Dwi Wiraningsih; Lukita Ambarwati (Program Studi Matematika Universitas Negeri Jakarta, 2023)
Word of mouth marketing based on community brands makes companies target communities that are in accordance with product characteristics so that word of mouth marketing becomes more effective. This thesis focuses on modeling and analyzing word of mouth marketing based on brand community. Model consists of five variables, namely Susceptible, Infected, Community, Positive, and Negative. The model is analyzed by determining the equilibrium point which produces two equilibrium points, namely the equilibrium point obtained when there are no infected individuals and the equilibrium point obtained when there are infected individuals. The simulation uses data that has been obtained from one of the companies in Indonesia, with the basic reproduksi number is 950,1458877.